2010
DOI: 10.3855/jidc.984
|View full text |Cite
|
Sign up to set email alerts
|

Slime layer formation and the prevalence of mecA and aap genes in Staphylococcus epidermidis isolates

Abstract: Introduction: Staphylococcus epidermidis strains are frequently associated with catheter-related infection, acute bacteremia, and hospitalacquired infection. Some isolates produce an extracellular matrix called slime that may make them more resistant to antibiotics. The aim of this study was to determine antimicrobial resistance patterns, the prevalence of slime production, and the distribution of genes (mecA and aap, respectively) associated with these phenotypes in S. epidermidis nasal isolates from health-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
2
19
3
Order By: Relevance
“…MRSA isolates that were resistant to multiple antibiotics were mostly biofilm producers, so it can be concluded that the majority of MDR pathogens are likely biofilm producers or vice versa. This result is in accordance with other studies [31,32]. Most hospital-acquired MRSA are also resistant to numerous other antibiotics.…”
Section: Discussionsupporting
confidence: 93%
“…MRSA isolates that were resistant to multiple antibiotics were mostly biofilm producers, so it can be concluded that the majority of MDR pathogens are likely biofilm producers or vice versa. This result is in accordance with other studies [31,32]. Most hospital-acquired MRSA are also resistant to numerous other antibiotics.…”
Section: Discussionsupporting
confidence: 93%
“…This is while some sensitive isolates also have mecA gene. The underlying cause of this discrepancy between phenotype and genotype can be pointed the mutations, which leads to palindrome defect in -10 region of mecA promoter (13). Moreover, it was mentioned that the clinical isolates from the ICU wards had shown the highest number of HVR types.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, catheter-related infections are associated with increased mortality and contribute to an increased length of hospital stay and higher healthcare costs, which are problematic in limited-resource settings such as South Africa [12,13]. In three different hospitals Iran, nasal swabs were collected from 163 healthcare workers; 96 were cultured and resulted positive for S. epidermidis [14]. Similar results were reported in a study performed between 2000 and 2009 in a hospital in Kenya, where in blood samples collected from neonates, S. epidermidis accounted for 33% of the isolated strains [15].…”
Section: Staphylococcus Epidermidis Spreadmentioning
confidence: 99%